Pengaruh Kurikulum Merdeka Terhadap Kualitas Belajar Peserta Didik Di Sekolah Dasar - Yuliana Pujiningsih; Isnaini Wahyuningrum; Arum Emilia Salikha; Maulida Nurkhaliza; Afifah Fatin Pratiwi; Sri Suwartini (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This research is based on the background of the previous curriculum, students have just mastered the learning process, then a new curriculum with a somewhat different character from the previous curriculum appears. Where in this independent curriculum students are required to be more active and creative in the learning process so that the quality of learning will be a little heavier than before. This study aims to determine the influence of the independent curriculum on the quality of learning of elementary school students. This type of research is a literature study or literature review. The data was taken from using scientific journals found on Google Schoolar and other journal sites that are relevant to the application of the independent curriculum to the quality of learning of students in elementary schools. Changes in the curriculum can have a positive and negative impact on the quality of education. The positive impact is that educators are more creative and innovative in learning. The existence of an independent curriculum also makes it easier for students to develop their interests and potential.